The Impact of Job Turnover (Termination, Resignation, Retirement and Disability) on the Quality Service at McDonald's Restaurants - Alhyasat, Khaled M.K.; Al-Gharaibeh, Shehadeh Mofleh; Alhyasat, Waleed M. K.; AL-Drawi, Yazan Yousif Taleb; Korany , Hossam (Journal of Posthumanism, 2025)
The study aims to examine the effect of job turnover on quality service. A quantitative cross-sectional approach was utilized in this study, employing a questionnaire to assess the perspectives of Jordanian employees regarding the structures of the study model. sample was 303 employees. The present study employs the Structural Equation Modelling (SEM) approach, utilizing AMOS as the chosen method of analysis. The findings of the research indicate that a significant and positive relationship between resignation, retirement, and disability with Quality Service at McDonald's Restaurants in Jordan. However, the study also reveals a negative impact of termination on quality service. The study's theoretical framework was built upon four robust variables, namely Termination, Resignation, Retirement, and Disability. One of the contributions is to investigate the four factors that contribute to job turnover, rather than focusing on just one dimension. Additionally, these dimensions have an impact on the quality of service provided.